PENGARUH HASIL ALTMAN Z-SCORE, SPRINGATE, DAN ZMIJEWSKI SEBAGAI ALAT PREDIKSI KEBANGKRUTAN FINANCIAL DISTRESS) TERHADAP HARGA SAHAM (Studi Empiris Perusahaan Property & Real Estate dan Food and Beverages yang Terdaftar di Bursa Efek Indonesia Periode 2014 - Rilla Gantino; Goei Ivan Jonathan (Universitas Tridinanti, 2020)
ABSTRACKThe study aimed to analyze the effect of results Altman Z-Score, Springate, and Zmijewski on stock price in the property & real estate and food and beverage industry which are lised in Indonesia Stock Exchange (IDX) in the period 2014-2018. Hypothesis testing result showed that partially the results Altman Z-Score have a effect on stock price property & real estate and food and beverage companies. Partially the results Springate have a effect on stock price property & real estate and food and beverage companies, and the results Zmijewski have a effect on stock price food and beverage companies, however does not have effect on stock price property & real estate companies. Keywords: Altman Z-Score, Springate, Zmijewski, and Stock Price